20 Improving the documentation of lumbar punctures in children. (31st October 2017) - Liu, Lucy; Potter, Jane; Williams, Sam
Abstract : The Royal Alexandra Children's Hospital in Brighton treats over 45 000 patients a year, provides inpatient and outpatient care and has a dedicated paediatric emergency department which is open 24 hours a day, seven days a week. Lumbar puncture is a useful diagnostic tool in children, and forms part of the septic screen in a febrile child. We found that although the procedure was commonly done in the emergency department and on the general medical wards, documentation of the procedure was poor and led to ambiguity in the interpretation of blood glucose results. Whilst there have been proposals for proformas to be used in adult medicine to promote best practice and to increase patient safety, there has been little evidence of proformas being used in the paediatric population. One study in Australia had shown improvement in the documentation of lumbar punctures after introduction of a proforma and teaching sessions for junior doctors. We identified 11 important paramaters to be documented after a lumbar puncture, and designed a novel proforma with these parameters included. We then promoted the use of the proformas with educational sessions and trust-wide e-mails. Overall documentation significantly improved after the introduction of the proforma from 60% to 75%. Two of the initially worst documented parameters were consent (initially documented 33.3% of the time) and a paired glucose level (initially documented 37.5% of the time) and these increased to a documentation rate of 86% and 100% respectively, when the proforma was used. These changes have also been sustained. A re-audit one year after the initial audit showed the proforma was still being used for 65% of lumbar punctures and that those who used the proforma have better levels of documentation than those that did not. In conclusion, the use of the proforma has improved the documentation of lumbar punctures in paediatric patients at the Royal Alexandra Children's Hospital.